Preparation of Multiwalled Carbon Nanotubes/Hydroxyl-Terminated Silicone Oil Fiber and Its Application to Analysis of Crude Oils - Shukui Zhu; Ting Tong; Wanfeng Zhang; Wei Dai; Sheng He; Zhenyang Chang; Xuanbo Gao (The Scientific World Journal)
A simple and efficient method to analyze the volatile and semivolatile organic compounds in crude oils has been developed based on direct immersion solid-phase microextraction coupled to comprehensive two-dimensional gas chromatography/time-of-flight mass spectrometry (DI-SPME-GC × GC/TOFMS). A novel fiber, multiwalled carbon nanotubes/hydroxyl-terminated silicone oil (MWNTs-TSO-OH), was prepared by sol-gel technology. Using standard solutions, the extraction conditions were optimized such as extraction mode, extraction temperature, extraction time, and salts effect. With the optimized conditions, a real crude oil sample was extracted and then analyzed in detail. It shows that the proposed method is very effective in simultaneously analyzing the normal and branched alkanes, cycloalkanes, aromatic hydrocarbons, and biomarkers of crude oil such as steranes and terpanes. Furthermore, the method showed good linearity (r > 0.999), precision (RSD < 8%), and detection limits ranging from 0.2 to 1.6 ng/L.